2013
DOI: 10.1042/bj20121422
|View full text |Cite
|
Sign up to set email alerts
|

The mannose 6-phosphate-binding sites of M6P/IGF2R determine its capacity to suppress matrix invasion by squamous cell carcinoma cells

Abstract: The M6P (mannose 6-phosphate)/IGF2R (insulin-like growth factor II receptor) interacts with a variety of factors that impinge on tumour invasion and metastasis. It has been shown that expression of wild-type M6P/IGF2R reduces the tumorigenic and invasive properties of receptor-deficient SCC-VII squamous cell carcinoma cells. We have now used mutant forms of M6P/IGF2R to assess the relevance of the different ligand-binding sites of the receptor for its biological activities in this cellular system. The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 43 publications
(84 reference statements)
0
14
0
Order By: Relevance
“…Studies have shown that abnormal proliferation, invasion and migration of tumor cells are common conditions in malignant tumors (2932). Therefore, the ability of tumor invasion and migration is a detrimental biological feature of malignant tumors, and it is also the most prominent clinical manifestation of malignant tumors (33). It has been found that overexpression of STC2 promotes CRC tumorigenesis by activating the AKT/ERK signaling pathway (26).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that abnormal proliferation, invasion and migration of tumor cells are common conditions in malignant tumors (2932). Therefore, the ability of tumor invasion and migration is a detrimental biological feature of malignant tumors, and it is also the most prominent clinical manifestation of malignant tumors (33). It has been found that overexpression of STC2 promotes CRC tumorigenesis by activating the AKT/ERK signaling pathway (26).…”
Section: Discussionmentioning
confidence: 99%
“…M6PR is a multifunctional membrane-associated protein involved in trafficking of soluble lysosomal proteins in the cytoplasm and binding of M6P-containing ligands, such as insulinlike growth factor 2 (IGF2; ref. 24). Importantly, it is a receptor for granzyme B (GrzB) secreted by activated cytotoxic T cells (CTL; ref.…”
Section: Introductionmentioning
confidence: 99%
“…4b). Further, we reconstituted an Igf2r mutant murine SCC-VII squamous cell carcinoma line ( Igf2r KO)27 with either wild-type human IGF2R (IGF2R) or a mutant version inactive for M6P binding (IGF2R*)28. As ricin itself exhibits OMT N-glycan structures29, we used the IGF2R* mutant cell line to exclude possible binding of ricin to IGF2R via M6P.…”
mentioning
confidence: 99%